Identification of novel GNAS mutations in intramuscular myxoma using next-generation sequencing with single-molecule tagged molecular inversion probes - Elise M. Bekers; Astrid Eijkelenboom; Paul Rombout; Peter van Zwam; Suzanne Mol; Emiel Ruijter; Blanca Scheijen; Uta Flucke (BMC, 2019)
Abstract Background Intramuscular myxoma (IM) is a hypocellular benign soft tissue neoplasm characterized by abundant myxoid stroma and occasional hypercellular areas. These tumors can, especially on biopsy material, be difficult to distinguish from low-grade fibromyxoid sarcoma or low-grade myxofibrosarcoma. GNAS mutations are frequently involved in IM, in contrast to these other malignant tumors. Therefore, sensitive molecular techniques for detection of GNAS aberrations in IM, which frequently yield low amounts of DNA due to poor cellularity, will be beneficial for differential diagnosis. Methods In our study, a total of 34 IM samples from 33 patients were analyzed for the presence of GNAS mutations, of which 29 samples were analyzed using a gene-specific TaqMan genotyping assay for the detection of GNAS hotspot mutations c.601C > T and c602G > A in IM, and 32 samples using a novel next generation sequencing (NGS)-based approach employing single-molecule tagged molecular inversion probes (smMIP) to identify mutations in exon 8 and 9 of GNAS. Results between the two assays were compared for their ability to detect GNAS mutations with high confidence. Results In total, 23 of 34 samples were successfully analyzed with both techniques showing GNAS mutations in 12 out of 23 (52%) samples. The remaining 11 samples were analyzed with either TaqMan assay or smMIP assay only. The TaqMan assay revealed GNAS mutations in 16 out of 29 samples (55%), with six samples c.601C > T (p.R201C; 38%) and ten samples c.602G > A (p.R201H; 62%) missense mutations. The smMIP assay identified mutations in 16 out of 28 samples (57%), with five samples c.601C > T (p.R201C; 31%) and seven samples c.602G > A (p.R201H; 44%) missense mutations. In addition, four samples (25%) revealed novel IM-associated mutations, including c.601C > A (p.R201S), c.602G > T (p.R201L), c.602G > C (p.R201P) and c.680A > G (p.Q227R). Combining the results of both tests, 23 out of 34 sporadic IM samples (68%) showed a GNAS mutation. Conclusions Both the TaqMan and the smMIP assay a show a high degree of concordance in detecting GNAS hotspot mutations in IM with comparable sensitivity. However, since the NGS-based smMIP assay permits mutation detection in whole exons of GNAS, a broader range of GNAS mutations can be identified by the smMIP approach.